Diagnostic performance of the Cobas MTB and Logix Smart MTB for diagnosing pulmonary and extrapulmonary tuberculosis: a cross-sectional study of diagnostic tests - Miguel Hueda-Zavaleta; Juan Carlos Gomez de la Torre; Diana Minchón-Vizconde; Claudia Barletta-Carrillo; Cesar Copaja-Corzo; Gustavo Tapia-Sequeiros; Cinthya Flores; Cristian Piscoche; Cecilia Miranda; Ada Mendoza; Vicente A. Benites-Zapata (Therapeutic Advances in Infectious Disease, 2024)
Background: Molecular tests have contributed to reducing the mortality rate through early and accurate diagnosis of tuberculosis (TB). This is due to their low processing complexity and diagnostic accuracy superior to conventional methods. Objective: To evaluate the diagnostic performance of Cobas MTB and Logix Smart MTB compared to Xpert MTB/RIF Ultra for pulmonary tuberculosis (PTB) and extrapulmonary tuberculosis (EPTB). Design: A cross-sectional study of diagnostic tests was carried out in a clinical laboratory in Lima, Peru. Methods: All pulmonary and extrapulmonary samples from patients with presumptive TB who had been subjected to smear microscopy, Xpert MTB/RIF Ultra, Cobas MTB, Logix Smart MTB, and mycobacteria culture were included to determine their diagnostic performance. Results: A total of 175 samples were included, 102 (58.3%) of pulmonary origin and 73 (41.7%) of extrapulmonary origin. Among the total samples, 19 (10.9%) had positive cultures (all were pulmonary samples), 48 (27.4%) had positive Xpert MTB/RIF Ultra results, 45 (25.7%) had positive Cobas MTB results, and 36 (20.6%) had positive Logix Smart MTB results. The agreement between Cobas MTB and Logix Smart with the Xpert MTB/RIF Ultra was 97.1% and 93.8%, respectively. Compared to Xpert MTB/RIF Ultra, the area under the curve/receiver operating characteristic and sensitivity of the Cobas MTB and Logix Smart methods were 0.95 and 91.7%, and 0.90 and 81.0%, respectively. Conclusion: Cobas MTB and Logix Smart presented adequate performance for diagnosing pulmonary and extrapulmonary tuberculosis comparable to the Xpert MTB/RIF Ultra.